Association of dietary risks, behavioural and lifestyle factors, and the magnitude of disability burden among Australian cancer patients: An observational epidemiology study. (June 2022) - Mahumud, Rashidul Alam; Sultana, Marufa; Gow, Jeff; Rahman, Md. Ashfikur; Uddin, Khandakar Farid; Kamal, Mostafa; Alam, Khorshed; Dawson, Angela; Law, Chi Kin
Abstract: Background: Cancer patients are confronted with a variety of other health-related issues, including physical disability, poor quality of life, and psychological challenges. This study aims to quantify the association of dietary, behavioural and lifestyle risk factors and comorbidities on the magnitude and distribution of disability burden among cancer patients in Australia. Methods: This study comprised a sample of 2283 cancer patients drawn from the latest nationwide Australian National Health Survey conducted in 2017–18. Negative binomial regression models were used to estimate the incidence rate ratio (IRR) of the number of disabilities and its associations. Results: Forty-five percent of cancer patients experienced at least one disability. The magnitude of disability was significantly associated with sugar-sweetened drink consumption ≥ 3 days per week (IRR= 1.12, 95% CI: 1.02–1.26), a lack of physical activity (IRR = 1.69, 1.38–2.07), frequent or regular alcohol consumption (IRR = 1.95, 1.84–2.08), poor health status (IRR = 1.99, 1.78–2.24) and the presence of five or more chronic comorbid conditions (IRR = 3.59, 2.90–4.46). Cancer patients who consumed vegetables at least two or more times per day had a 10% lower risk of disability burden (IRR = 0.90, 0.82–0.99). Conclusions: This study shows the association of diet, behavioural, and lifestyle risk factors on the degree of disability burden among cancer patients, highlighting the need for bold and effective policies. The findings will inform the implementation of evidence-based lifestyle interventions and offer a foundation for evaluating their influence on cancer survivors' health. Highlights: Cancer patients often experience a variety of other long-term health burdens. Sugar-sweetened drinks and poor lifestyles increase the risk of ill health in cancer patients. Minimising unhealthy behaviours are a priority to achieve better survivorship. Evidence-based lifestyle interventions are a priority for this high-risk population.